AVALIAÇÃO DA PREVALÊNCIA DA ASMA APÓS INTERVENÇÃO EDUCATIVA NA ATENÇÃO BÁSICA: Uma experiência em comunidade quilombola - SÁ FILHO, João Batista Carlos de (2024)
Introduction: Asthma is a highly prevalent chronic respiratory disease, and in Brazil, it is considered one of the highest in the world. Underdiagnosis and overdiagnosis are common in all health services, but the issue is particularly concerning in primary care, where the "Inverse Care Law" prevails, especially in quilombola communities. Objective: To carry out an educational intervention on asthma in primary care in a quilombola community. Methods: The research uses a qualitative and quantitative, interventionist approach and is conducted at a primary health unit in Itapecuru-Mirim, Maranhão. Three technical products were applied: a medical care guide, an asthma patient card, and an educational video about asthma. Results: Of the 355 screened participants, 41% showed indications of asthma. The analysis revealed a prevalence ranging from 10.98% to 68.42%. The intervention resulted in 37 new diagnoses, whereas previously only two patients were recognized as asthmatic in the community. Additionally, diagnosed patients received guidance, an asthma monitoring card, and watched educational videos. Conclusion: The educational interventions proved effective in expanding asthma diagnosis and raising disease awareness in vulnerable communities, standing out as a replicable and economically viable strategy for primary care in Brazil.